A new species of Euploca (Boraginales: Heliotropiaceae) from the Inter-Andean dry valleys of Bolivia - Wood, John R.i.; Muñoz-Rodríguez, Pablo (Phytotaxa, 2022)
Euploca riochiquensis is described and illustrated as a species new to science endemic to the Rio Chico valley in Chuquisaca, Bolivia. Morphologically it resembles E. lagoense in its solitary axillary flowers but differs conspicuously in its shrubby habit. Its phylogenetic position, conservation status and distribution are discussed.